Mosquito repellency of the seeds of celery (Apium graveolens L.) - Tuetun B. (2014)
When the mosquito repellencies of four fractions of Apium graveolens seeds (one hexane, two dichloromethane and one methanolic) were investigated in the laboratory, all four were found to offer human volunteers some protection against female, adult Aedes aegypti. The hexane fraction, however, was found to exhibit the highest repellency in the laboratory, with median effective doses (ED50) and ED95 of 0.41 and 2.93 mg/cm2 skin, respectively. Only this fraction, which was also found to provide protection against mosquito bites for 3.5 h when applied, in the laboratory, at a concentration of 250 mg/ml, was then investigated for its repellency in the field and its stability. In storage, it was found to retain its repellency for at least 2 months, although significant reductions in its repellency were observed (in terms of shortened complete-protection times) after 3 months, whatever the temperature of storage (-20°C, 4°C, or room temperature). When applied to the skin of volunteers under field conditions, the hexane fraction showed strong repellent activity against a wide range of mosquito species belonging to various genera (Ae. gardnerii, Ae. lineatopennis, Armigeres subalbatus, Culex tritaeniorhynchus, Cx. vishnui group, Cx. quinquefasciatus and Mansonia uniformis). It appeared not to cause dermal irritation or any other adverse effect, either during 6 months of use or in the following 3 months of follow-up. Mosquito repellents based on extracts of Ap. graveolens seeds could be developed commercially, as an effective personal-protection measure against mosquito bites and the diseases caused by mosquito-borne pathogens.